Advancements in therapeutic drugs targeting of senescence. (October 2020) - Zhu, Mingsheng; Meng, Ping; Ling, Xian; Zhou, Lili
Aging leads to a high burden on society, both medically and economically. Cellular senescence plays an essential role in the initiation of aging and age-related diseases. Recent studies have highlighted the therapeutic value of senescent cell deletion in natural aging and many age-related disorders. However, the therapeutic strategies for manipulating cellular senescence are still at an early stage of development. Among these strategies, therapeutic drugs that target cellular senescence are arguably the most highly anticipated. Many recent studies have demonstrated that a variety of drugs exhibit healthy aging effects. In this review, we summarize different types of drugs promoting healthy aging – such as senolytics, senescence-associated secretory phenotype (SASP) inhibitors, and nutrient signaling regulators – and provide an update on their potential therapeutic merits. Taken together, our review synthesizes recent advancements in the therapeutic potentialities of drugs promoting healthy aging with regard to their clinical implications.